Respostas

A melhor resposta!
2014-08-10T17:22:02-03:00
a) 2x²-5x-3=0
A=2
B= -5         (DELTA)= (-5)²-4 (2.-3)        X= - (-5) +/- (RAIZ DE DELTA)
C= -3          (DELTA)= 25-4(-6)                         2.2
                 (DELTA)= 25 + 24
                 (DELTA)= 49                      X= 5 +/- 7
                                                              4
                                                         X'= 5+7= 12= 3
                                                                4      4
                                                         X''= 5-7= -2= -1
                                                                4     4     2

b) x² + x-12=0       
A=1                          (DELTA)= 1² - 4 (1.-12)
B=1                          (DELTA)= 1 + 48
C=-12                      (DELTA)= 49
   
X= -1 +/- (RAIZ DE DELTA)
       2.1

X= -1 +/- 7
     2

X'= -1+7= 6=3
        2     2

X''= -1 -7= -8 = -4 = - 4
         2     2      1

c)-x²+x-6=0 ( -1)
A= -1       (DELTA)= ( -1)² - 4 ( 1.-6)
B= 1       (DELTA)= 1 +24
C= -6       (DELTA)= 25

X= - ( 1) +/- (RAIZ DE DELTA)
                     2. -1

X= -1 +/- 5
      -2
X'= -1 + 5 = +4  = -2    ( + DIVIDIDO POR - É IGUAL A - )
      -2        -2
X''= -1 -5 = -6 = +3     ( - DIVIDIDO POR - É IGUAL A + )
       -2      -2


1 5 1